Global Dynamics of an HTLV-1 Model with Cell-to-Cell Infection and Mitosis - Sumei Li; Yicang Zhou (Abstract and Applied Analysis)
A mathematical model of human T-cell lymphotropic virus type 1 in vivo with cell-to-cell infection and mitosis is formulated and studied. The basic reproductive number R0 is derived. It is proved that the dynamics of the model can be determined completely by the magnitude of R0. The infection-free equilibrium is globally asymptotically stable (unstable) if R0<1  (R0>1). There exists a chronic infection equilibrium and it is globally asymptotically stable if R0>1.